6z-3=z+12

Simple and best practice solution for 6z-3=z+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z-3=z+12 equation:


Simplifying
6z + -3 = z + 12

Reorder the terms:
-3 + 6z = z + 12

Reorder the terms:
-3 + 6z = 12 + z

Solving
-3 + 6z = 12 + z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
-3 + 6z + -1z = 12 + z + -1z

Combine like terms: 6z + -1z = 5z
-3 + 5z = 12 + z + -1z

Combine like terms: z + -1z = 0
-3 + 5z = 12 + 0
-3 + 5z = 12

Add '3' to each side of the equation.
-3 + 3 + 5z = 12 + 3

Combine like terms: -3 + 3 = 0
0 + 5z = 12 + 3
5z = 12 + 3

Combine like terms: 12 + 3 = 15
5z = 15

Divide each side by '5'.
z = 3

Simplifying
z = 3

See similar equations:

| -2x^2-14x+8=0 | | 12x+3-5=x-(x+1) | | (x+5)(2x-10)=180 | | 7+85=197 | | (2x-1)+(3y+2)i=5-4i | | 8(3x+8+2y)=24 | | 16=8-x+5 | | 3x-6+x+2+2x=180 | | 4X+6=2(X+3)+2 | | a^2-10ab-39b^2=0 | | 6x+(-30x)=72 | | h=-16t^2+48t+1408 | | 6+2x-3=21x+9 | | 79=49-y+y | | 4b-3(3-4b)=7 | | 9(y-4)=5y-32 | | 5y-9+y+55=7y+50-3y | | 7a+3b=1 | | 3b+4=-7b+11 | | 7a-3b=1 | | Q=180-5p | | 9x-3+8x=2x+4-4x | | f(x)=5x^4+12x^3+-16x^2+10 | | 6.5w=-123.5 | | 9x-7x=36 | | -2x-2=50x-50 | | 6x+7x+9x=88 | | 10-3=x-9 | | R=F+460 | | 2x+y=1.25 | | 5x+2x=154 | | 6x+(-78)-30x=-6 |

Equations solver categories